2017
DOI: 10.1007/s00428-017-2076-4
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy after transcatheter aortic valve implantation

Abstract: Autopsy after transcatheter aortic valve implantation (TAVI) is a new field of interest in cardiovascular pathology. To identify the cause of death, it is important to be familiar with specific findings related to the time interval between the procedure and death. We aimed to provide an overview of the autopsy findings in patients with TAVI in their medical history divided by the timing of death with specific interest in the added value of autopsy over a solely clinically determined cause of death. In 8 Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…[7][8][9] The incidence of clinical PVE after TAVR spans between 0.6% and 3%, [6,[8][9][10] although autopsy studies show a rate closer to 12%. [4] The median age at diagnosis was 80 years. [8,11] Respiratory infections, and dental and urologic procedures were the leading source for bacteremia, [6,9,10,12] though in half of the patients, the source of infections could not be identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] The incidence of clinical PVE after TAVR spans between 0.6% and 3%, [6,[8][9][10] although autopsy studies show a rate closer to 12%. [4] The median age at diagnosis was 80 years. [8,11] Respiratory infections, and dental and urologic procedures were the leading source for bacteremia, [6,9,10,12] though in half of the patients, the source of infections could not be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Prosthetic valve endocarditis (PVE) after TAVR is a rare but very serious and often deadly complication. [4] Surgical valve replacement (SVR) remains the cornerstone treatment for complicated PVE. However, the patients undergoing TAVR are often elderly and have complex comorbidities which may eventually preclude or substantially increase the risk of SVR.…”
Section: Introductionmentioning
confidence: 99%
“…Durability in TAVI is related to the biological nature of the valve leaflets and to pre-procedural steps, such as valve crimping and intravalvular balloon inflation, which is essential for a transcatheter delivery. Several reports have been recently published showing specific lesions (transverse fractures and longitudinal cleavages) on pericardial leaflets, especially in balloon-expandable valves (24)(25)(26)(27), phenomena that can potentially lead to valve deterioration. Unfortunately, longterm durability data after TAVI are still not available in the literature and just a few reports present results in patients with 5-year follow-up (28) that, for valve prosthesis, are not considered sufficient.…”
Section: Valve Durabilitymentioning
confidence: 99%
“…[3,7] These distinctive features of TAVI-IE can delay diagnosis and therapy and have even led to postmortem diagnosis only. [12] Recent studies have shown that 18 F-fluorodeoxyglucose positron emission tomography (¹⁸F-FDG PET ) uptake around surgical valves is an accurate indicator of PVE and case series described its applicability in TAVI-IE. [11] However, there are no systematic and large scale data for computed tomography (CT) or ¹⁸F-FDG PET evaluation in patients with suspected TAVI-IE.…”
Section: Introductionmentioning
confidence: 99%